FLORIAN MEISENBERG. - Kamin, Diana (Art in America, 2013)
The article reviews the art exhibition "Faith so certain shall never be shaken by heaviest sorrow," which will feature various paintings, installations and digital videos by the German-born, New York City-based contemporary artist Florian Meisenberg, held at the Simone Subal gallery in New York City, in 2013.